Divine Management in the Holy Quran ( An Objective Study ) - Zorao , Mahmood (Islamic Sciences Journal, 2023)
ABSTRACT Divine management are a broad and thorny topic that deals with all areas of the life of creatures, and through this topic man reaches the knowledge of Allah Almighty and his ability to manage the affairs of his own creation, Thus the man understands an unimportant area of the philosophy of existence and life, so he sees what is good and right for him and for all creatures, and this is a stimulus to be in harmony with the system of the universe and the life and in accordance with the methodology wanted by Allah Almighty. and Divine management have motives including (building belief, guiding, supporting the believers and the oppressed, lessons, organizing and managing the affairs of creatures). Knowing about the management is the cornerstone of the formation of the righteous and reformer person, as well as the family and society, and it is a way to the happiness of humanity in this world and the hereafter, so it is one of the priorities of the human knowledge.